Test of a prototype Microstrip Silicon Detector for the FOOT experiment. Issue 1 (1st November 2022) - Silvestre, G; Di Ruzza, B; Ambrosi, G; Movileanu, M; Kanxheri, K; Barbanera, M; Placidi, P; Servoli, L
Abstract : The FOOT (FragmentatiOn Of Target) experiment aims to measure the fragmentation cross-section of protons into H, C, O targets at beam energies of interest for hadrontherapy (50-250 MeV for H and 50-400 MeV/u for C ions). Given the short range of the fragments, an inverse kinematic approach requiring precise tracking capabilities in a magnetic volume has been chosen. A key subsystem of this experiment will be the Microstrip Silicon Detector, based on 3 X-Y measuring station, each composed of two 150 μm thick single side microstrip sensors. In this work, we present the results of characterization of the new version of a 64 channel low-noise/low power high dynamic range readout ASIC and subsequent tests of the first 150 um thick sensor prototype. A series of tests were also performed to validate a novel "grazing angle" approach, where it is possible to change the track length below a given strip varying the incoming particle's incident angle onto the sensor to test the electronics dynamic range without using high Z ions.